Synthesis of 7-Hydroxy-4-methyl Coumarin Under Microwave Irradiation - Liu, Shujing; Zhao, Bin; Jiang, Qingmei; Wang, Yanen (Asian Journal of Chemistry, 2014)
The 1,3-benzenediol and ethyl acetoacetate as raw materials were used to synthesize 7-hydroxy-4-methyl coumarin under microwave irradiation with zirconium sulfate tetrahydrate as the catalyst. Experiment showed that the yield reached up to 87.5 %, when the reaction conditions were as follow: the molar ratio of phenolic and ester was 1.0:1.0, 0.4 g of Zr(SO4)2·4H2O, 10 mL of cyclohexane, the mixtures react 12 min under 500 W microwave radiation.